A personal leadership statement (2023)
A personal leadership statement. As university students and future professionals, we aspire to become leaders who inspire and empower others to reach their full potential. We want to lead by example and create a positive impact on the people and organizations we work with. We aim to be visionaries who can communicate clear and compelling visions for the future and motivate others to work towards achieving them. Additionally, we want to cultivate a culture of trust, respect, and collaboration, where everyone feels valued and has a sense of ownership in achieving common goals. “Being a leader shows us that difficulties are opportunities to grow and inspire others by showing them how great they are.” Harold González Monsalve, Natalia Pérez Varilla & Andrés Isaza Blanco.